Epidemiology of digestive parasites in buffaloes from Romania - BĂRBURAȘ, DA; GYORKE, A; POP, LM; BĂRBURAȘ, R; MIRCEAN, V; COZMA, V (Journal of the Hellenic Veterinary Medical Society, 2022)
Digestive parasites are a constraint on buffalo productivity. Data regarding the prevalence of parasitic diseases in buffaloes are reported in developed countries, but in Romania, they are missing. The aim of this study was to evaluate the prevalence of internal parasites in buffaloes raised in households and farms from Romania. Faeces samples were collected from 180 buffaloes of different ages (calves: 0-6 months; juveniles: 6-30 months; adults:> 30 months). The faecal samples were processed by coproparasitological methods: flotation, sedimentation, and McMaster. Digestive parasites were detected in 57.2% of buffaloes. Most buffaloes had single species infection(42.2%) (p<0.001), and only 15.0% had infection with 2 (14.5%) or 3 (0.6%) parasites. The prevalence of digestive parasites was higher in calves (68.8%) and juveniles (76.9%) compared with adults (19.6%) (p<0.001). Eimeria spp. (43.3%), Buxtonella sulcata(1.7%), Fasciola hepatica(4.4%), Paramphistomum cervi(2.8%), Moniezia spp. (0.6%), Toxocara vitulorum (11.7%), digestive strongyles (3.3%), Strongyloides papillosus (5.0%), and Capillaria spp. (0.6%) were identified. Eimeria spp. and T. vitulorumwerethe most prevalent parasitesin calves and juveniles(p<0.001). F. hepatica was the most prevalent parasite in adults.Eimeria spp. and S. papillosus were the only infections diagnosed in farmed buffaloes, with a higher prevalence (p>0.05) than in household buffaloes. B. sulcata, Moniezia spp., T. vitulorum and S. Papillosus were diagnosed only in young buffaloes, while Capillaria spp. only in adults. The OPG of Eimeria spp. was higher in young buffaloes compared with adults (p<0.001). Age was the risk factor identified for infections with Eimeria spp., T. vitulorum and F. hepatica.